MOF-derived Co3O4-ZnO heterostructure for 3-methyl-1-butanol detection - Santos, Gustavo S.M. [UNESP]; de Sá, Bruna S. [UNESP]; Perfecto, Tarcísio M.; Volanti, Diogo P. [UNESP] (Elsevier, 2024)
Microbial volatile organic compounds (MVOCs) detection with a fast response and high selectivity is barely studied. The challenge is developing a material that matches these factors in different sensing conditions, such as operating temperature and humidity. In this study, we searched for a better way to improve the gas sensing properties of cobalt oxide (Co3O4), synthesizing a MOF-derived (ZIF-67-ZIF-8) p-n heterojunction of Co3O4-ZnO and varying the molar concentrations of these metals. The Co3O4 was synthesized through a mixture of cobalt(II) nitrate hexahydrate and 2-methylimidazole in a simple process at room temperature, forming the ZIF-67, which was then calcinated. The Co3O4-ZnO and ZnO-Co3O4 heterostructures were synthesized by adding zinc(II) nitrate hexahydrate to produce ZIF-8 and create a heterojunction with ZIF-67, followed by calcination. The Co3O4-ZnO sample exhibited higher sensing performance than pure Co3O4 and the heterostructure ZnO-Co3O4. In this case, Co3O4-ZnO exhibited a higher response of 14.6 to 3-methyl-1-butanol (3M1B) with a selectivity ratio of 2.79. These findings could improve food control by monitoring the MVOCs produced by bacteria, such as Pseudomonas spp, in the spoilage process of shrimp. Furthermore, under 65% of relative humidity, this sensor demonstrated a response of 10.4. Therefore, improving the Co3O4 performance as a gas sensor was achievable with a p-n heterojunction of zinc and cobalt, indicating a suitable response under different conditions.
Keywords: 3-methyl-1-butanol; Cobalt oxide; Gas sensor; Metal-organic framework; Semiconductor